2020
DOI: 10.1002/jac5.1315
|View full text |Cite
|
Sign up to set email alerts
|

“To be or not to be in the ward”: The impact of COVID‐19 on the role of hospital‐based clinical pharmacists—A qualitative study

Abstract: Introduction: The coronavirus disease 2019 (COVID-19) pandemic has significantly affected health care systems around the world. In many hospitals and health care facilities, services and health care workers have been reorganized and restructured to meet the demands of the pandemic. The impact of the pandemic on hospital-based clinical pharmacists and their ability to deliver pharmaceutical care is currently unknown. Objective: This study aimed to explore the impact of the COVID-19 pandemic on hospital-based cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 21 publications
3
36
0
7
Order By: Relevance
“…In many cases, the pharmaceutical care work was provided because the medical team actively invited pharmacists to participate, and pharmacists did not participate proactively. The findings are similar to a qualitative study conducted in Malaysia ( 20 ). In this study, Chinese pharmacists participated in treating COVID-19 patients through telemedicine.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In many cases, the pharmaceutical care work was provided because the medical team actively invited pharmacists to participate, and pharmacists did not participate proactively. The findings are similar to a qualitative study conducted in Malaysia ( 20 ). In this study, Chinese pharmacists participated in treating COVID-19 patients through telemedicine.…”
Section: Discussionsupporting
confidence: 87%
“…One study examined strategies to strengthen the role of community pharmacists in public health ( 19 ). Another study discussed the impact of the COVID-19 pandemic on clinical pharmacists working in Malaysian hospitals and how clinical pharmacy is considered a health care service ( 20 ). These three qualitative studies introduced the non-traditional roles of pharmacists, the roles of pharmacists in public health, and the influence of pharmaceutical care under public health crises from pharmacists' perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The responses of hospital pharmacy to COVID-19 have been described in the USA, 6 9 China, 7 Australia 10 and Malaysia. 11 While many of these responses matched those employed at UHB and KCH, there were examples of differing practice.…”
Section: Discussionmentioning
confidence: 96%
“…Cheong researched the experiences of clinical pharmacists whose ward-based role was withdrawn, due to COVID-19, in Malaysia. 11 Concerns were raised about the perception of the need for a clinical pharmacy service by the wider hospital. This concern was not observed at UHB or KCH and may be due to well-established clinical pharmacy services in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…In Western Australia, community pharmacists delivering vaccination services were also denied receiving any financial remuneration from the government [ 21 ]. Onozato et al pointed out the significance of administrative and political support within healthcare institutions to maintain the quality of clinical pharmacy services [ 89 ]. Bauman demonstrated that pharmacists did not get proper acknowledgement during COVID-19 like other frontline fighters.…”
Section: Global Recognition Of Pharmacists In Covid-19mentioning
confidence: 99%